2018
DOI: 10.1109/tbcas.2018.2871470
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Design of Efficient Ultrasonic Power Links for Scaling Towards Submillimeter Implantable Receivers

Abstract: We present an analytical framework for optimizing the efficiency of ultrasonic wireless power links for implantable devices scaled down to sub-mm dimensions. Key design insights and tradeoffs are considered for various parameters including the operating frequency, the transmission depth, the size of the transmitter, the impedance and the aperture efficiency of the miniaturized receiver, and the interface between the receiver and the power recovery chain on the implant. The performance of spherically focused tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…In this work, it is suggested that it would be possible to deliver at least half the power to the receiver by reducing the size of the piezoelectric to 0.5 mm 3 while keeping the same input power intensity. Later, the same research group developed an end-to-end design for a sub-mm implantable receiver with a high efficiency single crystalline piezoelectric material that resonate in the range of 1−2 M Hz [93]. They obtained a maximum efficiency of 1.93 − 0.23% for an implantation depth ranging from 6 to 10 cm and for a receiver width of 0.6 mm.…”
Section: B Apt Links In Biomedical Applicationsmentioning
confidence: 99%
“…In this work, it is suggested that it would be possible to deliver at least half the power to the receiver by reducing the size of the piezoelectric to 0.5 mm 3 while keeping the same input power intensity. Later, the same research group developed an end-to-end design for a sub-mm implantable receiver with a high efficiency single crystalline piezoelectric material that resonate in the range of 1−2 M Hz [93]. They obtained a maximum efficiency of 1.93 − 0.23% for an implantation depth ranging from 6 to 10 cm and for a receiver width of 0.6 mm.…”
Section: B Apt Links In Biomedical Applicationsmentioning
confidence: 99%
“…Similar to the series resonant frequency, characterization of Γ at the parallel resonant frequency of the piezo is also of interest as described in Section II. Air is sometimes used as a backing layer of the implant piezo [24] to reduce mechanical losses and enhance the electro-acoustical efficiency of the implant piezo in exchange for a more complex implant assembly and larger implant volume. Therefore, here we provide closed-form expressions for Γ(Z E ) to include: 1) Γ's dependence on Z E at both the series and parallel resonant frequencies 2) the effect of low-Q mechanically damped piezo, and 3) the effect of air-backing.…”
Section: Simplified Implant Piezo Modelmentioning
confidence: 99%
“…ere are several techniques to realize WPT, such as ultrasound, optical, microwave radiation, electric field coupling, and inductive coupling [10][11][12][13][14][15][16][17][18]. Among these methods, inductive coupling is the most preferred for IMDs, where power is transmitted from one coil and received by the other (usually integrated with the IMD inside a human body) through electromagnetic induction.…”
Section: Introductionmentioning
confidence: 99%